PENGARUH IMPLEMENTASI TIME AND MOTION STUDY DAN BIAYA BAHAN BAKU TERHADAP BIAYA FINISHING PRODUK PADA DEPARTEMEN FINISHING PT HARRISON & GIL JAVA SEMARANG - Nadia Nurin Fajrina; Taviyastuti Taviyastuti; Rustono Rustono (Politeknik Negeri Semarang, 2019)
The aim of this research is to analyze the influence of the implementation of time and motion study and material cost on finishing cost. The amount of population is 33 woodenfurnitureproductsTheanalysismethodofthisresearchispathanalysiswithtwo stepregressionmodel.TheresultoffirststructuralequationisLaborCost=0,630TMS, andthesecondstructuralequationisFinishingCost=0,285MaterialCost+0,347TMS +0,370LaborCost.AccordingtotheAdjustedRSquareresultonthefirstequation,time and motion study implementation contributes 37,8% on labor cost, while 62,2% is explained by other variable outside this research. Meanwhile time and motion study implementation,laborcostandmaterialcostcontribute56%onthefinishingpricewhile 44% is explained by other variable outside thisresearch